Antiviral Pills against SARS-CoV-2 Virus to Combat Future Epidemic Threats in Pakistan: Antiviral Pills to Combat Future Epidemics in Pakistan - Ayesha Khan; Hadia Batool; Shaheen Shahzad (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Antiviral pills are oral medications that treat infections through the inhibition of the viral growth and replication cycle. Paxlovid by Pfizer and Molnupiravir by Merck are the two pills effective for high-risk SARS-CoV-2 patients. Paxlovid works by inhibiting the replication cycle of SARS-CoV-2 using cysteine residues in-vitro. These cysteine residues inhibit the main protease of the virus by functioning as reversible covalent inhibitors. Molnupiravir works by introducing a high rate of mutations in the viral RNA causing the virus to become biologically unstable and non-functional. Both antiviral drugs can bridge the gap in the preparedness for viral outbreaks in low-income countries like Pakistan by mitigating the chances of fatality and inpatient treatment in high-risk, unvaccinated individuals. Pakistan has been plagued by various epidemics over the years however SARS-CoV-2 outbreak caused many deaths along with an economic crisis. The country lacks the resources to endure high inpatient treatment rates in case of SARS-CoV-2 infections, which is why the need for antiviral pills like Paxlovid and Molnupiravir is empirical to overcome epidemics and viral outbreaks. This work outlines the antiviral pills and their efficacy against SARS-CoV-2 with a focus on how these drugs can overcome significant gaps in epidemic preparedness and response in Pakistan. We aim to highlight how antiviral pills against SARS-CoV-2 can ensure resilience to future epidemic threats in Pakistan.